Bio-distribution and bio-availability of silver and gold in rat tissues with silver/gold nanorod administration. Issue 22 (29th March 2018) - Wu, Meiyu; Chen, Liang; Li, Ruiru; Dan, Mo; Liu, Haining; Wang, Xinsheng; Wu, Xiaochun; Liu, Ying; Xu, Liming; Xie, Liming
Abstract : Along with the increasing applications of nanomaterials in medical fields, to know the systemic distribution of nanomaterials in the body through a precise method is required for the biosafety assessment of nanomaterials. Abstract : Along with the increasing applications of nanomaterials in medical fields, to know the systemic distribution of nanomaterials in the body through a precise method is required for the biosafety assessment of nanomaterials. In this study, we firstly have established a reliable inductively coupled plasma mass spectrometry (ICP-MS) method for concentration measurement of silver (Ag) and gold (Au) in biological tissues. Then, based on this method, the Ag or Au distribution in rat blood and almost all of the organs were analyzed after an i.v. or s.c. administration of Au@Ag NRs. Both the time-dependent contents of Ag and Au in blood and two pharmacokinetic models confirmed the rapid clearance of Ag from blood. At 24 h after i.v. injection, there was the highest level of Ag in liver, followed by portal nodes, spleen, lung, bone marrow and pancreas. In addition, we also found there were gender-related distributions of Ag and Au in some organs, especially after s.c. injection. Therefore, these more comprehensive and important results would give fundamental information for the biological risk assessment of nanomaterials.